2011
DOI: 10.1103/physrevlett.107.113002
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Turnstiles as a Chaotic Ionization Mechanism in Rydberg Atoms

Abstract: We present an experimental and theoretical study of the chaotic ionization of quasi-onedimensional potassium Rydberg wavepackets via a phase-space turnstile mechanism. Turnstiles form a general transport mechanism for numerous chaotic systems, and this study explicitly illuminates their relevance to atomic ionization. We create time-dependent Rydberg wavepackets, subject them to alternating applied electric-field "kicks", and measure the electron survival probability. Ionization depends not only on the initial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The passive advection of particles in a twodimensional fluid flow is a well-studied problem important both for its direct relevance to fluid mixing and for its broader connection to Hamiltonian dynamics. The latter finds applications ranging from chaotic ionization in atomic physics [1][2][3][4][5][6][7] to the motion of asteroids in the solar system 8 . A key observation in passive chaotic advection is that particular curves-the invariant manifolds-form barriers to particle transport [9][10][11][12] .…”
mentioning
confidence: 99%
“…The passive advection of particles in a twodimensional fluid flow is a well-studied problem important both for its direct relevance to fluid mixing and for its broader connection to Hamiltonian dynamics. The latter finds applications ranging from chaotic ionization in atomic physics [1][2][3][4][5][6][7] to the motion of asteroids in the solar system 8 . A key observation in passive chaotic advection is that particular curves-the invariant manifolds-form barriers to particle transport [9][10][11][12] .…”
mentioning
confidence: 99%
“…Such systems span a broad range of length scales and include global weather patterns [3], mixing of fluids [4][5][6], and firing of neurons [7]. One mesoscale system that has been used recently to study nonlinear dynamics and chaos is the kicked Rydberg atom [8][9][10][11], i.e., a high-n atomic state that is subject to a series of electric field pulses [termed half-cycle pulses (HCPs)] with durations τ k T n , where T n is the electron Kepler period. In this regime, each HCP simply delivers an impulsive momentum transfer, or "kick," to the excited electron given by p = F(t)dt, where F(t) is the force exerted on the electron as a result of the applied HCP.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the geometric structures present in the phase space of a Rydberg atom subject to external electric field pulses of alternating sign, i.e., alternating between kicks toward and away from the nucleus. Earlier work indicated that ionization in this system is controlled by a geometric structure of phase space called a turnstile, which promotes electrons from bound to ionized states during one kicking cycle [10,12]. (For another example of turnstile-mediated ionization, see…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations